A synthesis model for forcing action arrangement in the system of reducing dynamic loads of a mobile machine - Kaźmierczak, Henryk; Pawłowski, Tadeusz; Zembrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
An idea is presented for a method to lower excessive dynamic loads in the system of supporting structure, mechanical-hydraulic forcing system, vibration isolation system, protective unit. The dynamic characteristics of the system are determined by the method of dynamic susceptibility. An analytical model of the system was built (mobile machine to carry out protective treatments; project WDN-POIG.01.03.01-00-164/09).
Keywords: structural changes; dynamic susceptibility; forcing system model; dynamic mobility